2018
DOI: 10.1161/atvbaha.118.311298
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a Promotes Vascular Smooth Muscle Cell Calcification by Downregulating SIRT1 (Sirtuin 1) and Axl (AXL Receptor Tyrosine Kinase)

Abstract: Objective- Vascular calcification (VC) is age dependent and a risk factor for cardiovascular and all-cause mortality. VC involves the senescence-induced transdifferentiation of vascular smooth muscle cells (SMCs) toward an osteochondrogenic lineage resulting in arterial wall mineralization. miR-34a increases with age in aortas and induces vascular SMC senescence through the modulation of its target SIRT1 (sirtuin 1). In this study, we aimed to investigate whether miR-34a regulates VC. Approach and Results- We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 55 publications
2
105
0
5
Order By: Relevance
“…Consequently, Sirt1 possesses the characteristic of anti-calcification and plays a key role in perpetuating VC [79]. By the way, microRNA-34a promotes VC by downregulating AXL receptor tyrosine kinase (Axl) and Sirt1, resulting in VSMCs senescence and mineralization [80].…”
Section: Sirt1 Attenuates the Osteoblastic Phenotypic Transition Of Vmentioning
confidence: 99%
“…Consequently, Sirt1 possesses the characteristic of anti-calcification and plays a key role in perpetuating VC [79]. By the way, microRNA-34a promotes VC by downregulating AXL receptor tyrosine kinase (Axl) and Sirt1, resulting in VSMCs senescence and mineralization [80].…”
Section: Sirt1 Attenuates the Osteoblastic Phenotypic Transition Of Vmentioning
confidence: 99%
“…Among them, 15 (40.5%) have been confirmed or are suspected to promote or aggravate VC in different scenarios, while 22 (59.5%) protect against VC formation or progression. Direct gene targets have been identified for 14 miRNAs with negative VC regulatory capacity, including miR-29a/29b [14], miR-29b-3p [34], miR-30b [16,47], miR-30c [16], miR-30e [25], miR-34b/34c [29,64], miR-125b [13,22] miR-133a [19], miR-135a [30], miR-182 [42], miR-204 [15,41,50], and miR-205 [21], while few direct targets have been identified for miRNAs with VC enhancement ability (miR-34a [39], miR-128-3p [48], and miR-135a-3p [17]). In the following sections, we describe the clinical features of each VC-regulating miRNA based on their propensity for positive or negative vascular influences.…”
Section: Mirnas In Vc: Positive and Negative Vc Regulatorsmentioning
confidence: 99%
“…In VSMCs, miR-34b/34c has been shown to attenuate VC severity through down-regulating special AT-rich sequence-binding protein 2 (SATB2) and subsequently RUNX2 expression levels [29], while down-regulating miR-34b in VSMCs also leads to enhanced calcification [64]. On the contrary, Badi et al focused on the role of miR-34a in the pathogenesis of VC using miR-34 knockout mice [39]. They found that such genetically manipulated mice receiving vitamin D had less soft tissue and aortic calcification compared to wildtype littermates, and the effect was mediated through miR-34-dependent sirtuin 1 (SIRT1) suppression.…”
Section: Mirnas With Controversial Influences On Vcmentioning
confidence: 99%
“…Не без основания можно говорить о том, что предшественник семейства эффек- торных молекул микро-РНК miR-34a связан с сосудистой кальцификацией и ее стимуляцией. Это, в свою очередь, включает вызванную старением трансдифференцировку клеток гладких мышц сосудов, ингибируя при этом пролиферацию клеток и, таким образом, приводя к минерализации артериальной стенки [39]. Следовательно, клетки гладких мышц сосудов играют решающую роль в старении сосудов и образовании аневризмы восходящей грудной аорты.…”
Section: дезадаптивное повреждение сосудистой стенки при старенииunclassified